Human Rhinoviruses in Pediatric Patients in a Tertiary Care Hospital in Germany: Molecular Epidemiology and Clinical Significance - Franziska Neugebauer; Sandra Bergs; Uwe Gerd Liebert; Mario Hönemann (Viruses, 2022)
Rhinoviruses (RVs) constitute a substantial public health burden. To evaluate their abundance and genetic diversity in pediatric patients, RV RNA in respiratory samples was assessed using real-time RT-PCR and partial nucleic acid sequencing of viral genomes. Additionally, clinical data were retrieved from patient charts to determine the clinical significance of pediatric RV infections. In total, the respiratory specimens of 776 patients (<18 years), collected from 2013 to 2017, were analyzed. Infections occurred throughout the entire year, with peaks occurring in fall and winter, and showed remarkably high intra- and interseasonal diversity for RV genotypes. RV species were detected in the following frequencies: 49.1% RV-A, 5.9% RV-B, and 43.6% RV-C. RV-C was found to be more frequently associated with asthma (p = 0.04) and bronchiolitis (p < 0.001), while RV-A was more frequently associated with fever (p = 0.001) and pneumonia (p = 0.002). Additionally, 35.3% of the patients had co-infections with other pathogens, which were associated with a longer hospital stay (p < 0.001), need for ventilation (p < 0.001), and pneumonia (p < 0.001). Taken together, this study shows pronounced RV genetic diversity in pediatric patients and indicates differences in RV-associated pathologies, as well as an important role for co-infections.